(untitled) (Journal of Universal Science Research, 2024)
This article explores the concept of class-centered teaching as a systematic approach to decision-making within educational settings. It emphasizes the centrality of the classroom environment in shaping teaching strategies, curriculum design, and learning outcomes. By integrating pedagogical theories with practical classroom applications, this framework supports teachers in making informed, student-centered decisions.